Gut microbiota profiling of aflatoxin B1-induced rats treated with Lactobacillus casei Shirota - Liew, Winnie Pui Pui; Sabran, Mohd Redzwan; Than, Leslie Thian Lung (MDPI, 2019)
Aflatoxin B1 (AFB1) is a ubiquitous carcinogenic food contaminant. Gut microbiota is of vital importance for the host’s health, regrettably, limited studies have reported the effects of xenobiotic toxins towards gut microbiota. Thus, the present study aims to investigate the interactions between AFB1 and the gut microbiota. Besides, an AFB1-binding microorganism, Lactobacillus casei Shirota (Lcs) was tested on its ability to ameliorate the changes on gut microbiota induced by AFB1. The fecal contents of three groups of rats included an untreated control group, an AFB1 group, as well as an Lcs + AFB1 group, were analyzed. Using the MiSeq platform, the PCR products of 16S rDNA gene extracted from the feces were subjected to next-generation sequencing. The alpha diversity index (Shannon) showed that the richness of communities increased significantly in the Lcs + AFB1 group compared to the control and AFB1 groups. Meanwhile, beta diversity indices demonstrated that AFB1 group significantly deviated from the control and Lcs + AFB1 groups. AFB1-exposed rats were especially high in Alloprevotella spp. abundance. Such alteration in the bacterial composition might give an insight on the interactions of AFB1 towards gut microbiota and how Lcs plays its role in detoxification of AFB1.